Uji Efikasi Ekstrak Daun Mengkudu, Kemangi dan Jambu Biji dalam Menghambat Pertumbuhan Cendawan Colletotrichum gloeosporioides pada Buah Pepaya - Susanti, Sari; Kusmiadi, Riwan; Aini, Sitti Nurul (Universitas Bangka Belitung, 2017)
Anthracnose disease is a crucial problem in the cultivation of papaya. It is caused by C.gloesporioides. one way to overcome this problem was by using natural fungicides. Some of the natural substances that have natural fungicides as their property are noni, basil, and guava. The research was conducted at the Microbiology laboratory of the Faculty of Agriculture, Fisheries, and Biology of Universitas Bangka Belitung January to April 2016. The research utilizes Randomized Analysis Complete Design with Factorial structure. The first factor are the extracts (E), consists of noni leaves (E1), basil leaves (E2), and guava leaves (E3). The second factor are the concentrations of the extract, consists of 0% (K0), 10% (k1), 20% (K2), 30% (K3), 40% (K4), 50%(K5), and 60% (K6). The data was analysed using analysis of variance at Î± 5%, with the used of SAS Program (Statistical Analytic System), if the effect was found significant, the data was further analysed using DMRT (Duncan Multiple Range Test). The research result showed that the extract of guava leaves at 30% concentration provided the best result in inhibiting the growth of C.gloesporioides in papaya.